Unsteady characteristics of lubricating oil in thrust bearing tank under different rotational speeds in pumped storage power station. (December 2022) - Zhang, Yuquan; Sun, Jie; Zheng, Yuan; Ge, Xinfeng; Peng, Xuyi; Hong, Yunlai; Fernandez-Rodriguez, E.
Abstract: Oil mist accumulation and leakage in hydropower generator bearings are common. However, they undermine not only the operational safety and stability of the generator but also the balance of living organisms downstream of rivers. Most studies on oil flow patterns are based on steady flow field simulations, which may result in potential errors particularly due to initial and unforeseen velocity increases. The unsteady multiphase flow numerical simulation method was used to calculate the motion behavior of lubricating oil in thrust bearing tanks at different rotating speeds. The variations in lubricating oil flow, pressure distribution characteristics, velocity, temperature, oil level, and vorticity at different times were obtained. The results show that the flow and pressure field distributions in an oil tank are mainly affected by the rotation of the thrust head and mirror plate and by the cooling circulation method, respectively. The lubricating oil motion becomes a function of gravity, centrifugal force, and Coriolis force. The oil surface of the volume fraction exhibited periodic motion around the tank and a climbing movement in the oil-retaining ring and oil slinger. The oil-retaining ring performs well at a speed of 500 rpm; however, minute oil droplets and mist rapidly spread in the tank due to violent oil fluctuations. Large vortices with periodic oil surfaces are also observed in regions with high turbulence intensity owing to shear and centrifugal forces. The method and framework presented can be used to optimize the structural design of thrust bearing assembly and reduce the formation of oil and gas mixtures.